Testing hypotheses by using optimal statistical criteria. II - Kuk, Yu. V.; Petunin, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the structure of the critical function of an optimal statistical criterion for testing an arbitrary finite set of simple alternative hypotheses.